What Does Scholarship on Institutionalizing Urban Climate Action Say? - Ama Kissiwah Boateng (European Scientific Journal, ESJ, 2023)
With in-depth knowledge of the urban climate governance literature, this paper reviews the relevant scholarship on institutionalizing climate action in cities and urban areas to understand which aspects are well-researched, providing guidance to scholars in the field. The results show that articles addressing urban climate adaptation make up a large of the selected literature. The analysis has identified ideas about how innovation may be reinforced. Therefore, one critical step is to explicitly investigate how global North and South cities are testing new institutional arrangements and experimenting with adaptation and mitigation policies, plans, and processes as they seek to develop and advance their climate goals.